The incorporation of toys in the public library an evaluation study - Bagunu, Jessie Rose M.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The objectives of this study were to determine the propriety of incorporating toys in the Quezon City Public Library; to evaluate the developmental effectiveness of toys in the library where children are able to manipulate and play with them and to know the problems encountered with the inclusion of toys in the library.
In the study, survey method was used with 40 students as the respondents. In addition, the study used the experimental method with children aged 2-6 years old as its participants.
Based on the data gathered from the survey and interviews, respondents (77.5 percent) are more satisfied with the collection of the Quezon City Public Library if toys are included for children. The observation among children determined toys' developmental effectiveness where:1. Children learned the process of socialization through interaction. Children were able to interact with other people including friends, playmates and classmates. Through interaction, those young children formed relationships with one another that is, meeting and making friends.2. The library urged the children to explore that they see around them and to discover new things through toys, which was provided and displayed for them to discover new things through toys, which was provided and displayed for them to manipulate and play with.3. The researcher noticed that the puzzle is a way of challenging the children if they take things apart, they are responsible for putting them back together, With this kind of activity and type of toy, children were taught of mastering a skill on how to solve a problem.4. In addition, the toys helped the children to developmentally by encouraging them to count and identify objects that are familiar and unfamiliar to them.5. Through toys, children learned to be creative and used their minds by forming and creating things and objects out of the clay and the lego sets provided in the study.
In the study, provided and displayed among the shelves are the open-ended and realistic toys, most of the children preferred the open-ended toys (blocks, clay, puzzles and lego sets) because of its skill-driven and manipulative feature. However, children also played the realistic toys after they got bored with the open-ended toys.
The only problem encountered during the study was the volume of the children's voices especially when they were with friends and playmates. The need for the Children's Corner expansion is evident and preferably, the place should be secluded for children to have all the freedom to play so as not to disturb other researchers of the library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Quezon City Public Library; Toy lending libraries -- Philippines -- Quezon City